Aristotle’s "Rhetoric": A Pragmatist Analysis of Persuasive Interchange - Prus, Robert (Qualitative Sociology Review, 2008)
Approaching rhetoric as the study of persuasive interchange, this paper considers the relevance of Aristotle's Rhetoric for the study of human group life. Although virtually unknown to modern day social scientists, this text has great relevance for contemporary scholarship. Not only does Aristotle's text centrally address influence work (and resistance), identities and reputations, deviance and culpability, emotionality and deliberation, and the broader process of human knowing and acting in political, character shaping, and courtroom contexts, but Aristotle also deals with these matters in remarkably comprehensive, systematic, and precise terms. Attending to the human capacity for agency, Aristotle also works with a sustained appreciation of purposive, reflective, adjustive interchange. Hence, whereas this text is invaluable of as a resource for the comparative transhistorical analysis of human interchange, it also suggests a great many ways that contemporary scholarship could be extended in the quest for a more adequate, more authentic social science.